2020
DOI: 10.1037/tra0000909
|View full text |Cite
|
Sign up to set email alerts
|

Yoga for veterans with PTSD: Cognitive functioning, mental health, and salivary cortisol.

Abstract: Objective: Research indicates that cognitive functioning is negatively impacted by exposure to chronic stress due to overactivation of the stress response. Yoga has demonstrated benefits when practiced by individuals diagnosed with posttraumatic stress disorder (PTSD). This quasi-experimental pilot study examined the impact of a yoga intervention on cognitive functioning, symptoms of PTSD, and the biological stress response in Veterans diagnosed with PTSD. Method: Cognitive functioning, self-report measures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…The moderate-to-large effect sizes in the TCTSY group are double those reported in other studies of trauma-sensitive yoga (TSY) with civilians 30 and veterans. 28 The effect sizes and CMDs in this study reflect within-group improvement. Davis et al recently reported on their large RCT of yoga for PTSD; however, while their control condition was active, it was not evidence based, and their effect size (0.46) was between yoga and a wellness intervention, rather than change within groups.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The moderate-to-large effect sizes in the TCTSY group are double those reported in other studies of trauma-sensitive yoga (TSY) with civilians 30 and veterans. 28 The effect sizes and CMDs in this study reflect within-group improvement. Davis et al recently reported on their large RCT of yoga for PTSD; however, while their control condition was active, it was not evidence based, and their effect size (0.46) was between yoga and a wellness intervention, rather than change within groups.…”
Section: Discussionmentioning
confidence: 56%
“…TCTSY, the experimental intervention in this RCT, was developed for civilian women survivors of complex trauma, specifically childhood sexual trauma, with chronic PTSD. 26,27 Studies of TCTSY with civilian women and veterans have effect sizes of 0.20-1.07, compared with no control, 28 wait list control, 29 and women's health education. 30 This 5-year study addresses the current gaps in knowledge of the effectiveness of yoga for PTSD and associated symptoms.…”
Section: Yoga As a Therapeutic Intervention For Ptsdmentioning
confidence: 99%
“…25 In a study with 34 veterans, Chopin and colleagues found that a trauma-informed yoga intervention was associated with a statistically significant reduction in PTSD symptoms, as did a study by Zaccari and colleagues with 17 veterans. 26,29 Justice and Brems also found some evidence that trauma-informed yoga interventions helped PTSD symptoms in a small sample of 4 veterans, although these results were not quantitatively analyzed. 27 In contrast, a small pilot study (n = 12) by Staples and colleagues testing a biweekly, 6-week yoga program did not show a significant effect on PTSD symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…18,[25][26][27][28][29] Participants consisted of veterans with chronic pain, post-9/11 veterans, female veterans of childbearing age, veterans with a history of trauma therapy, and other veterans. Types of exercise included moderate aerobic exercise and yoga.…”
mentioning
confidence: 99%
“…Another pre-post trial of a trauma-sensitive yoga intervention was undertaken by Zaccari et al (2020) among a smaller number of veterans with PTSD, which had a particular interest to determine outcomes not only for PTSD and other mental health symptoms but also for cognitive functioning and salivary cortisol. To our knowledge, this is the first published RCT of a yoga intervention to include salivary cortisol as an outcome.…”
Section: Special Issue Goals and Articlesmentioning
confidence: 99%